Sero-epidemiology of Crimean-Congo haemorrhagic fever in mixed crop-livestock farming households in Burkina Faso: a one health study - Abdoul Kader Ilboudo; Michel Dione; Ard M. Nijhof; Martin H. Groschup; Assana Cissé; Koala Lassane; Madi Savadogo; Laibané Dieudonné Dahourou; Kristina Roesel; Roch K. Dabiré; Zekiba Tarnagda; Bernard Bett (PLoS ONE, 2026)
Background Crimean-Congo haemorrhagic fever (CCHF) is a severe, widespread, tick-borne viral zoonotic infection. It is caused by an orthonairovirus that is transmitted by ticks. Sero-epidemiological studies in humans and livestock are valuable indicators of viral circulation and infection risk. This study aimed to investigate the seroprevalence and factors associated with CCHF virus exposure in humans and livestock in mixed crop-livestock farming households in rural Burkina Faso. Methods A cross-sectional animal-human linked study was conducted in 149 rural households across 16 randomly selected villages in two administrative regions of Burkina Faso. Human socio-demographic, livestock biodata, and serum samples were collected from household members and their livestock (cattle, sheep, and goats). Additional ecological and climatic data were extracted from online databases and merged with the field data. Serological testing was performed on human and animal samples using the ID Screen® CCHF Double Antigen Multi-species ELISA (IDvet, Grabels, France). Descriptive statistics and multivariable multilevel analyses were used to assess factors associated with exposure of cattle and small ruminants to CCHF virus, while the Fisher’s exact test was applied to assess the risk factors for human exposure. Results The study included 717 livestock farmers and 2,295 animals, comprising 666 cattle, 659 sheep and 970 goats. The overall CCHF virus (CCHFV) seroprevalence was 3.1% (95% CI: 1.9–4.6) in humans and 54% (95% CI: 50.2–57.7) in cattle. In small ruminants, the overall seroprevalence was 5.2% (95% CI: 4.2–6.4), with 9.1% (95% CI: 7.1–11.5) in sheep, and 2.5% (95% CI: 1.7–3.8) in goats. Farmers with inadequate livestock management-related biosecurity behaviour exhibited higher seroprevalence rates and an increased risk of CCHFV seropositivity. In cattle, seropositivity was positively associated with older age, female sex, longer grazing distances, and tick infestation. Seropositivity in small ruminants was associated with older age, being of the sheep species, and longer grazing distances. Ecological factors, including a higher aridity index in both cattle and small ruminants, and steeper slopes in cattle, were significant in univariate and multivariable analysis, respectively. The seroprevalence in both cattle and small ruminants showed significant clustering within households, with intra-cluster correlation (ICC) rates of 39% and 62%, respectively. Conclusion: This study highlighted that CCHFV is circulating among humans and their livestock in rural Burkina Faso. Individual and household-related risk factors, including socio-demographic, livestock management practices, and ecological characteristics, were identified. These findings provide valuable insights for designing tailored public health interventions towards strengthening CCHF surveillance and prevention among rural households.